2013
DOI: 10.1111/cas.12282
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic tumor volume by positron emission tomography/computed tomography as a clinical parameter to determine therapeutic modality for early stage Hodgkin's lymphoma

Abstract: Recent studies have shown that metabolic tumor volume (MTV) by positron emission tomography ⁄ computed tomography (PET ⁄ CT) is an important prognostic parameter in patients with non-Hodgkin's lymphoma. However, it is unknown whether doxorubicin, bleomycin, vinblastine, dacarbazine (ABVD) alone in early stage Hodgkin's lymphoma would lead to similar disease control as combined modality therapy (CMT) using MTV by PET ⁄ CT. One hundred and twentyseven patients with early stage Hodgkin's lymphoma who underwent PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 36 publications
(79 reference statements)
4
69
2
3
Order By: Relevance
“…[33] Nonetheless, our results corroborate those of several studies that reported a significant association between baseline PET-derived volumetrics and PFS in other lymphoma subtypes. [34][35][36][37][38][39][40][41] There was, however, no association between baseline SUV max and either PFS or response, in agreement with the results of another recent study in FL. [31] SUV is derived from a single measurement in Table 3.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[33] Nonetheless, our results corroborate those of several studies that reported a significant association between baseline PET-derived volumetrics and PFS in other lymphoma subtypes. [34][35][36][37][38][39][40][41] There was, however, no association between baseline SUV max and either PFS or response, in agreement with the results of another recent study in FL. [31] SUV is derived from a single measurement in Table 3.…”
Section: Discussionsupporting
confidence: 90%
“…[44] Consequently, the current literature does not yet provide evidence that the volume-derived indices MTV and TLG are superior to SUV max for predicting outcome in lymphoma. [35][36][37][38][39][40][41][42]45,46] In our analysis, the optimal cutoff for change in SUV was 60%, although dichotomization with a broad range of SUV cutoffs between 45% and 80% were also discriminative, with significant probability values. Notably, the degree of tumor response is a continuous variable, and thus response evaluation would be better with a continuous measurement method than a dichotomous one.…”
Section: Discussionmentioning
confidence: 60%
“…Preliminary results in small-or medium-sized series suggest that higher MTV may be independently associated with the outcome in HL [23,24] and DLBCL [25,26]. Similarly, high TLG has been independently associated with inferior outcomes in DLBCL [27].…”
Section: Potential Prognostic Role Of Baseline Pet/ctmentioning
confidence: 97%
“…In the other study an absolute SUV >2.5 was used for volume delineation. This led to overestimation of the metabolic volume by including voxels from the background which in patients with stage I/II HL resulted in finding a median TMTV higher than the median reported by Kanoun et al in patients with more advanced disease [14].…”
mentioning
confidence: 93%